Outbreak of mass mortality of yearling groupers of Epinephelus (Perciformes, Serranidae) associated with the infection of a suspected new enteric Sphaerospora (Myxozoa: Myxosporea) species in South China Sea. Issue 4 (19th December 2017) - Liu, X H; Xu, L W; Luo, D; Zhao, Y L; Zhang, Q Q; Liu, G F; Zhang, J Y
Abstract: A suspected new enteric Sphaerospora species was believed to be directly associated with the mass mortality of yearling groupers of Epinephelus spp. in South China. The epizootic generally emerged from late September to late April of the following year. The infection prevalence and mortality rate were significantly negatively correlated with fish size. Clinical signs included anorexia, cachexia and extrusion of white pulp‐like substance from anus after gentle pressure on the abdomen. Upon necropsy, severe intestinal oedema, thin and transparent intestinal wall, swollen spleen, kidney and gall bladder could be observed. Wet preparation of the infected samples showed large amount of typical disporous plasmodia of the genus Sphaerospora, but no mature spores were observed. Epidemiological investigation showed that this parasite exclusively infected Epinephelus groupers. Histopathologically, this species mainly infected the epithelium of intestine and kidney tubules and caused severe epithelia sloughing and the collapse of intestinal villus. Interestingly, this enteric myxosporidiosis did not cause severe emaciation of infected fish for mass mortality usually emerged within 2–3 days after appearance of clinical signs. The species was most genetically related to Sphaerospora fugu (89% sequence identity) and phylogenetically positioned within marine Sphaerospora lineage. This is the first report of enteric sphaerosporosis of groupers.